Altered glycosylation and sialylation of serum proteins and lipid bound sialic acids in chronic renal failure. - Kishore, B. K. (BMJ Group, 1983)
Abnormalities in the metabolism of carbohydrates, lipids and proteins are well documented in chronic renal failure (CRF). We have studied the extent of glycosylation and sialylation of serum proteins and also the levels of lipid-bound sialic acids in nondiabetic patients with CRF maintained on haemodialysis. The total neutral sugar content (TNS) and the non-enzymatic glycosylation (NEG) of serum proteins, the protein-bound sialic acids (PSA) and the lipid-bound sialic acids (LSA) were found to be significantly elevated in the patients as compared to a group of healthy controls. A single dialysis therapy produced some alterations in these measurements. The TNS correlated significantly with the NEG and also with the PSA. No correlation existed between total lipids. None of these measurements, however, correlated with the serum creatinine values. The established as well as putative pathophysiological consequences of these findings are discussed.